Perlindungan Hukum terhadap Anak Sebagai Pelaku Tindak Pidana dari Perspektif Kemerdekaan Pers - Kadek Mahadewi; I Wayan Rideng; Ida Ayu Putu Widiati (Jurnal Konstruksi Hukum, 2021)
Legal protection for children who consider the law is one important aspect that must be considered by all parties to avoid negative impacts felt by children and children. This research has two problemformulations, namely: 1) How is legal protection against children as a crime? 2) What are the implications of press freedom which violates children's rights as a crime? The method used is nonnative legal research. The implementation of press freedom in reporting is not in accordance with the regulations regarding child protection and the journalistic code of ethics because efforts are still being made by the press in reporting about children as a crime whose identity is published in both print and electronic media so that it has a negative impact both physically. and psychologically to children. This requires accountability from the press and sanctions given to the press who violate children's rights are regulated in the Criminal Code.